Dentin Bond Strength and Microleakage Comparison of Three Different Universal Adhesives - Seda Özkanoğlu; Gulsah Akin (Cumhuriyet University, 2021)
Objectives: The aim of this study is to compare the bond strengths and microleakage values of three different universal adhesive systems applied in self-etch to dentin. Materials and Methods: The study consists of two tests as the bond strength (SBS) test and microleakage test. In the SBS test, the mid-coronal dentin surfaces of forty-five human molars were exposed and randomly assigned into three groups [Single Bond Universal, Optibond XTR, and Tokuyama Universal] and adhesive systems were applied to dentin surfaces. The SBS test was performed after composite build-up. Then, the fracture surfaces were evaluated with a scanning electron microscope (SEM). In the microleakage test, identifical adhesive systems were applied to forty-five human premolars with fasial class V cavities were prepared as in the groups specified in the SBS. After composite resin restoration of cavities, the specimens were thermocycled for 500 cycles and then immersed in basic fuchsine, sectioned, and examined under a stereo-microscope. Data were evaluated using one-way ANOVA, Tukey's, Chi-square and Mann Whitney U tests. Results: Among the adhesives, the highest bond strength was achieved in Optibond XTR, while Tokuyama Universal showed the lowest (p<0.05). When evaluated for microleakage, no significant difference was reported in occlusal margins. In gingival margins, Optibond XTR showed less leakage compared to Tokuyama Universal (p<0.05). Conclusions: One-step universal adhesive systems did not show bond strength and leakage resistance that was as good as the two-step universal adhesive system.